Mindfulness as a Moderator in the Relation Between Income and Psychological Well-Being - Sugiura, Yoshinori; Sugiura, Tomoko (Frontiers in Psychology, 2018)
The relation between income and life satisfaction has been found to be weak, albeit positive (r = .10–.20). This study introduced psychological well-being as a dependent variable predicted by income in addition to life satisfaction. Furthermore, individual differences might determine the strength of this relation, that is, act as moderators. Thus, this study introduced mindfulness as one such possible moderator. Participants (N = 800, 50% women, aged 20–59 years) completed an Internet questionnaire. Of them, 734 reported income and were included in the analyses. Income had weak, yet positive, zero-order correlations with life satisfaction and psychological well-being (r = .13 and .11). Hierarchical regression controlling for demographics indicated that the relation between income and psychological well-being was moderated by mindfulness facets. Specifically, among those low in not judging or describing of experiences, psychological well-being was positively related to income. On the other hand, those high in these mindfulness dimensions indicated higher psychological well-being irrespective of income.